Habitat suitability for primate conservation in north-east Brazil. Issue 6 (28th November 2020) - Moraes, Bárbara; Razgour, Orly; Souza-Alves, João Pedro; Boubli, Jean P.; Bezerra, Bruna
Abstract: Brazil has a high diversity of primates, but increasing anthropogenic pressures and climate change could influence forest cover in the country and cause future changes in the distribution of primate populations. Here we aim to assess the long-term suitability of habitats for the conservation of three threatened Brazilian primates ( Alouatta belzebul, Sapajus flavius and Sapajus libidinosus ) through (1) estimating their current and future distributions using species distribution models, (2) evaluating how much of the areas projected to be suitable is represented within protected areas and priority areas for biodiversity conservation, and (3) assessing the extent of remaining forest cover in areas predicted to be suitable for these species. We found that 88% of the suitable areas are outside protected areas and only 24% are located in areas with forest cover. Although not within protected areas, 27% of the climatically suitable areas are considered priority areas for conservation. Future projections, considering a severe climate change scenario, indicate that A. belzebul, S. flavius and S. libidinosus may lose up to 94, 98 and 54% of their suitable range, respectively. The establishment of primate populations and their long-term survival in these areas are at risk. Mitigation actions such as the implementation of new protected areas, forest restoration and reduction of greenhouse gas emissions will be essential for the conservation of Brazilian primates.